Sonic injection into a PGM Pierce-Smith converter: CFD modelling and industrial trials - Chibwe, D.; Akdogan, G.; Bezuidenhout, G.; Kapusta, J.; Bradshaw, S.; Eksteen, Jacques (Published by The Southern African Institute of Mining and Metallurgy, 2014)
Peirce-Smith converters (PSCs) are extensively used in the copper, nickel, and platinum group metals industries to remove iron and sulphur from the molten matte phase. This technology has not changed significantly since its inception in the early 20th century. The typical converting operation involves lateral purging of air/oxygen-enriched air into molten matte through a bank of tuyeres. This blowing operation occurs at low air pressure from the blowers, and the induced bubbling regime is considered inefficient from both a process and an energy utilization perspective. Inherent drawbacks include recurrent tuyere blockage, inevitable tuyere punching operation to clear airways, and low oxygen efficiency as a result of substantial air losses due to leakages. Investigations in the 1980s demonstrated that jetting into Cu and Ni converters could reduce or eliminate some of the process difficulties. In spite of these findings, very little progress has been made in the application of these concepts for converting of non-ferrous melts on a commercial scale.As part of its operational improvement and energy reduction initiative, Western Platinum embarked on a full-scale industrial evaluation of generating a jetting regime by using sonic injection. Prior to full-scale industrial evaluation, a numerical assessment was conducted to ascertain the feasibility of implementing sonic injection on Lonmin converters. The work included flow characterization at high injection pressures achieving sonic velocity at the tuyere exit. The 2D and 3D simulations of the three-phase system were carried out using the volume of fluid (VOF) and realizable k-ε turbulence models to account for the multiphase and turbulence nature of the flow, respectively. These models were applied using the commercial CFD numerical code FLUENT. This paper discusses the key findings regarding understanding of gas plume extension, velocity distribution, shear wall stress analysis, and phase distribution characteristics in the system. Plant trials are also discussed with reference to the commercial aspects of a full-scale implementation of sonic injection in the smelter.